Peran Aktif Muhammadiyah dalam Meningkatkan Mutu Pendidikan Islam di Kabupaten Bombana Provinsi Sulawesi Tenggara - Melati, Anggun Putri; Noor Fuad, Ai Fatimah (CV. Creative Tugu Pena, 2024)
Muhammadiyah is an organization founded by KH. Ahmad Dahlan is a charitable business movement which to date has made many contributions in the field of education, especially Islamic education. Education is the foundation for humans in determining the direction of life, for this reason the education carried out must integrate religious knowledge and general knowledge in a balanced manner, so that it is in accordance with religious principles. The aim of this research is to reveal the active role and influence of Muhammadiyah starting from the background of its founding to its influence in improving the quality of Islamic education. The research method used is a qualitative method through interviews and literature study using historical methods. The data collection in this paper is by analyzing and exploiting books, documents, the internet and other relevant sources. This research concludes that the presence of Muhammadiyah in Bombana Regency is an enlightening movement that invites the purification of Islam as well as to eradicate thoughts of backwardness, poverty and ignorance. This effort is realized through the implementation of holistic education that integrates or combines general knowledge and religious knowledge to create intelligent and moral individuals. Thus, Muhammadiyah is committed to providing education that is more modern and in line with current developments. Keywords: Muhammadiyah Organization, Islamic Quality Education